2014
DOI: 10.15282/ijame.9.2014.3.0125
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Working Conditions of Heat Pump Components According to Running Modes

Abstract: In this study a detailed exergetic analysis is made of the components of heat pumps by changing the heat source and heat sink fluid as either water or air. To realize this aim a multifunctional heat pump test system was used, which can be run in four modes, air to air, air to water, water to air and water to water, using one compressor. When the system is run in water to air mode compressor exergy efficiency reaches its highest value. When the system is run in air to water mode the exergy efficiency of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Moreover, this research is only valid for condenser. Çakir and Çomakli [28] stated that the condenser is the component which needs to be improved compared to other components such as compressor and evaporator due to its low energy efficiency [28]. Table 1 shows the geometry configuration of condenser.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this research is only valid for condenser. Çakir and Çomakli [28] stated that the condenser is the component which needs to be improved compared to other components such as compressor and evaporator due to its low energy efficiency [28]. Table 1 shows the geometry configuration of condenser.…”
Section: Methodsmentioning
confidence: 99%
“…It was also observed that among the mixtures, M20 had the lowest power consumption which is 1.25 to 1.45% higher than R22. Exergy analysis of a heat pump using water and air was done by Cakir et al [32]. They found the highest compressor exergy efficiency while running the system in water to air mode.…”
Section: Introductionmentioning
confidence: 99%